Acyl-CoA:Lysophosphatidylethanolamine Acyltransferase Activity Regulates Growth of Arabidopsis. Issue 2 (13th April 2017) - Jasieniecka-Gazarkiewicz, Katarzyna; Lager, Ida; Carlsson, Anders S.; Gutbrod, Katharina; Peisker, Helga; Dörmann, Peter; Stymne, Sten; Banaś, Antoni
Abstract : The activity of LPEAT affects the growth of Arabidopsis and is essential for maintaining an adequate level of PE, LPE, and LPC in the cells. Abstract: Arabidopsis ( Arabidopsis thaliana ) contains two enzymes (encoded by the At1g80950 and At2g45670 genes) preferentially acylating lysophosphatidylethanolamine (LPE ) with acyl-coenzyme A (CoA), designated LYSOPHOSPHATIDYLETHANOLAMINE ACYLTRANSFERASE1 (LPEAT1) and LPEAT2. The transfer DNA insertion mutant lpeat2 and the double mutant lpeat1 lpeat2 showed impaired growth, smaller leaves, shorter roots, less seed setting, and reduced lipid content per fresh weight in roots and seeds and large increases in LPE and lysophosphatidylcholine (LPC ) contents in leaves. Microsomal preparations from leaves of these mutants showed around 70% decrease in acylation activity of LPE with 16:0-CoA compared with wild-type membranes, whereas the acylation with 18:1-CoA was much less affected, demonstrating that other lysophospholipid acyltransferases than the two LPEATs could acylate LPE . The above-mentioned effects were less pronounced in the single lpeat1 mutant. Overexpression of either LPEAT1 or LPEAT2 under the control of the 35S promotor led to morphological changes opposite to what was seen in the transfer DNA mutants. Acyl specificity studies showed that LPEAT1 utilized 16:0-CoA at the highest rate of 11 tested acyl-CoAs, whereas LPEAT2 utilized 20:0-CoA as the best acyl donor. Both LPEATs could acylate either sn position of ether analogs of LPC . The data show that the activities of LPEAT1 and LPEAT2 are, in a complementary way, involved in growth regulation in Arabidopsis. It is shown that LPEAT activity (especially LPEAT2) is essential for maintaining adequate levels of phosphatidylethanolamine, LPE, and LPC in the cells.